Masalah Sosial Dalam Novel Kubah Di Atas Pasir Karya Zhaenal Fananie: Kajian Sosiologi Sastra Dan Implementasinya Sebagai Pembelajaran Di Sma - Nugroho, Dhimas Aris, Dr. Nafron Hasyim (2016)
The research towards a novel entitled Kubah di Atas Pasir possessed three aims, they are; (1) Descripting structure that built the novel. (2) Descripting its social aspects (3) and the implementation inliterary study of Senior High School. This research including the qualitative descriptive research used the embedded case study to be at. The main source of this research is Kubah di Atas Pasir. The primary of this research are phrases, clauses, sentences, paragraphs and issue in the novel concerned the social issue. As well as the secondary data are taken from trusted online sources and articles applicable to support the research.The data collecting technique used in this research were the technique of library science, watch on and noting. The data analysis technique used in this research is the dialectics. The results of research already shown that the novel entitled Kubah di Atas Pasir written by Zhaenal Fananie has educational issue. This fictional work has main character namely Fatikha. This novel uses plotting forward. The novel also sets Ngurawan village as the main setting of the story. Some issues within the novel are educational issues, cultural issues, economical issues, leadership issues and environment issues as well. The results of research were going to be implemented in literary study of Senior High School (SMA) based on Kurikulum Tingkat Satuan Pendidikan (KTSP) Standar Kompetensi (SK) 7 rooted some aspects over folk tales and Indonesian literary works/translated novels.